Muscle bone-interaction during growth: influence of physical activity - G. Vicente-Rodríguez; I. Ara; J. Pérez-Gómez; C. Dorado; J.A. Serrano-Sánchez; J. A. L. Calbet (Asociación Española de Ciencias del Deporte, 2010)
To determine the independent effect of soft tissues on bone mineral content (BMC) and density (BMD), and how physical activity (PA) could affect these relationships, body composition by DXA, and the physical fitness (PF) were assessed longitudinally (3-yr) in 26 active and 16 non-active prepubertal boys. Significant advantage in the development of PF, muscle mass and total and lumbar spine BMC and total, lumbar spine and lower-limb BMD were found in the active compared with non-active boys.  Results imply that during puberty, lean mass development is the best predictor of bone mass accrual; and physical activity promotes bone acquisition by increasing lean mass but also by lean mass-independent mechanisms. PALABRAS CLAVE: health, body composition, development, exercise.